Difficulties and Countermeasures in Deep Processing of Sea Cucumber Viscera - Wenliang LIU; Yongbo ZHOU; Rongji ZENG; Yongjun SHAN; Shiying HUANG; Jian LI (Shipin gongye ke-ji, 2023)
Sea cucumber has many physiological functions, such as anti-tumor, anti-coagulation, anti-oxidation and immunity regulation. It has high edible and medicinal value, and has received much attention in nutrition and health care. There are few researches on the exploitation and utilization of sea cucumber viscera at home and abroad, and a lack of knowledge about the active components of sea cucumber viscera. The viscera of sea cucumber is often discarded as a by-product of processing and can not be fully utilized. At present, the utilization of sea cucumber viscera mainly focuses on the identification of active components and the removal of fishy products, and the research on the development of products is less. Based on the nutrients and active components of sea cucumber viscera, this paper expounds the processing and utilization of sea cucumber intestines, eggs, sperms, gonads and viscera, the establishment of removing fishy smell methods and the potential development direction of products from three aspects of papers, authorized patents and health food. In general, at present, there are generally shortcomings such as inconsistent processing methods of active components of sea cucumber offal and unclear practical ingredients of health food. With the development of processing technology, the comprehensive utilization of sea cucumber viscera by enzymatic hydrolysis and extraction will become an important direction.